Tahap Kesedaran Pekerja terhadap Aspek Keselamatan dan Kesihatan Pekerjaan : Satu Kajian di TNB Janamanjung Sdn. Bhd. - Norasyikin, Abdul Sani (2012)
This paper aims to investigate level of awareness among TNB Janamanjung Sdn. Bhd.(TNBJ) workers in relation to safety and health at work. They were chosen as respondent since they are exposed to risk, danger and hazards in the workplace such as accidents, coal dust and noise. One dependent variable is chosen namely level of awareness of occupational health and safety and three independent variables that is commitment; involvement of employees in Safety and Health Committee and safety and health training attended.Questionnaires have been used as an instrument and Statistical Package for Social Sciences (SPSS) version 19.0 software is used to analyze the data.Through analysis,the results showed that TNBJ’s employees have a high level awareness of occupational safety and health. The three independent variables have a significant influence on employee awareness and involvement in Safety and Health Committee were the most dominant variable.TNBJ’s Management should ensure occupational safety and health activities to be done regularly in order to sustain high level safety and health awareness among all staffs.For further research, it is recommended to conclude research to expand the study area throughout the wholly owned subsidiary of Tenaga Nasional Berhad (TNB).This will ensure more sample size of respondents and the result accuracy.